A colorimetric probe based on diketopyrrolopyrrole and tert-butyl cyanoacetate for cyanide detection1. (24th September 2015) - Wang, Lingyun; Zhu, Linhui; Cao, Derong
<x xml:space="preserve">Abstract</x> A new colorimetric probe 1 comprising a diketopyrrolopyrrole-based Michael receptor, which recognized cyanide anions with high selectivity, was designed and synthesized.